PENGARUH PEMBERIAN EM-4 TERHADAP LAJU DEKOMPOSISI LIMBAH PADAT KAMPUS SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATA PELAJARAN BIOLOGI SMA - M. Irsyad Fauzi; Suwondo Suwondo; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine how the effect of EM-4 on the rate of decomposition of solid waste at UNRI campus and its potential in producing Student Worksheet designs (LKPD) on waste and recycling material for class X even semester KD 3.11 and KD 4.11. This research was conducted from October to December 2020 at the Compost Shop in the Nature Laboratory of Biology Education, FKIP, Riau University. This study consisted of two stages, namely stage 1 field research with quantitative descriptive analysis to determine the effect of EM-4 on the rate of campus solid waste decomposition using 4 composting techniques, namely bokashi, drum, takakura and hollow brick techniques. Stage 2 of this research is to design LKPD with a design flow, namely Analyze (analysis) and Design (design). The results of the experimental stage research, Giving EM-4 affects the rate of decomposition of campus solid waste. The bokashi technique was the best media for composting that was carried out for 40 days with a decomposition rate of 1.15 g/day. Measurement of pH, temperature, humidity, C / N ratio and color of the 4 composting techniques meet the quality standards set by SNI: 19-7030-2004.Key words: Decomposition rate, EM-4, solid waste, LKPD design